Distal renal denervation: cardioprotection in patients with resistant hypertension - E. S. Sitkova; V. F. Mordovin; S. E. Pekarsky; T. M. Ripp; A. Yu. Falkovskaya; V. A. Lichikaki; I. V. Zyubanova; A. E. Baev; T. R. Ryabova; O. V. Mochula; V. Yu. Usov (Кардиоваскулярная терапия и профилактика)
Aim. To study the effectiveness of using the anatomically optimized distal renal denervation (RDN) in comparison with the standard approach for reducing myocardial damage and left ventricular (LV) hypertrophy in patients with resistant hypertension (HTN).Material and methods. The randomized double-blind study of the efficacy and safety of distal RDN compared to conventional main renal artery intervention (ClinicalTrials.gov NCT02667912) for the treatment of resistant HTN included 26 patients. All patients were divided into two groups: group 1 (n=16) — distal RDN, group 2 (n=10) — conventional RDN. In addition to 24-hour blood pressure (BP) monitoring, initially and 12 months after the intervention, contrast- enhanced cardiac magnetic resonance imaging was performed to determine the left ventricular mass and non-coronary myocardial damage area. All patients signed informed consent. Twenty-four patients completed the present study.Results. After 12 months, the mean 24-hour BP significantly decreased after both distal RDN (from 167,2±28,5/93,2±19,3 to 147,0±13,7/81,5±9,3 mm Hg (p<0,05)) and conventional RDN (from 157,5±22,5/90,6±23,9 to 139,9±17,7/80,0±16,7 (p<0,05)). Also in both cases, a trend to LV mass decrease was revealed: from 252,6±85,2 to 221,0±60,3 gm (p=0,096) after the distal RDN; from 214,3±54,1 to 186,4±48,1 gm (p=0,071) after the conventional RDN. In contrast, the myocardial damage area decreased only after distal RDN (from 2,33±1,33 to 1,35±0,67 cm3 (p=0,02)) and did not change after conventional RDN.Conclusion. In comparison with the conventional main renal artery intervention, distal RDN in patients with resistant HTN has an additional cardioprotective effect — a decrease in LV myocardial damage area.